2018
DOI: 10.1186/s12974-018-1319-x
|View full text |Cite
|
Sign up to set email alerts
|

α1-antitrypsin mitigates NLRP3-inflammasome activation in amyloid β1–42-stimulated murine astrocytes

Abstract: BackgroundNeuroinflammation has an essential impact on the pathogenesis and progression of Alzheimer’s disease (AD). Mostly mediated by microglia and astrocytes, inflammatory processes lead to degeneration of neuronal cells. The NLRP3-inflammasome (NOD-like receptor family, pyrin domain containing 3) is a key component of the innate immune system and its activation results in secretion of the proinflammatory effectors interleukin-1β (IL-1β) and interleukin-18 (IL-18). Under physiological conditions, cytosolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 67 publications
1
38
0
Order By: Relevance
“…and cation homeostasis, and cytoskeleton related processes (Table 3). Besides the expected oligodendrocyte compatible ones, the overrepresentation test indicated involvement of astrocyte and microglia related events such as glutamate metabolic process [23] and inflammatory response [24,25]. These data are consistent with the accepted view that CPZ induced oligodendrocyte loss is accompanied by expansion and activation of microglia and astrocytes [26].…”
Section: Plos Onesupporting
confidence: 88%
“…and cation homeostasis, and cytoskeleton related processes (Table 3). Besides the expected oligodendrocyte compatible ones, the overrepresentation test indicated involvement of astrocyte and microglia related events such as glutamate metabolic process [23] and inflammatory response [24,25]. These data are consistent with the accepted view that CPZ induced oligodendrocyte loss is accompanied by expansion and activation of microglia and astrocytes [26].…”
Section: Plos Onesupporting
confidence: 88%
“…We could not rule out the role of astroglia in LPS-induced sepsis-associated neurodegeneration. MCC950 also displayed the potency to repress astroglial NLRP3 inflammasome [91]. These findings highlight the promising application of NLRP3-IL-1β signaling inhibition in various neurodegenerative disorders.…”
Section: Roles Of Il-1β In Neuroinflammationmentioning
confidence: 69%
“…Moreover, astroglia can express NLRP3 inflammasome and IL-1β under certain conditions, such as in SOD1 mouse model of amyotrophic lateral sclerosis (ALS) and human sporadic ALS patients, and amyloid β 1-42 -stimulated murine astrocytes [90,91]. We could not rule out the role of astroglia in LPS-induced sepsis-associated neurodegeneration.…”
Section: Roles Of Il-1β In Neuroinflammationmentioning
confidence: 92%
“…In our experiments, however, Aβ 1-42 was applied together with BzATP for only 30 min, which is probably not enough time for an efficient induction of gene expression and protein synthesis. Other studies found that fibrillar and monomeric Aβ 1-42 can activate the NLRP3 inflammasome, thereby inducing the release of mature IL-1β [ 29 , 38 , 84 , 85 ]. This probably depends on the internalization of Aβ 1-42 fibrils via the scavenger receptor CD36, followed by lysosomal rupture, a known signal of NLRP3 assembly [ 29 , 86 , 87 ].…”
Section: Discussionmentioning
confidence: 99%